Towards promoting inclusion: analyzing our education environment and our intervention programme - Totoricagüena Barandica, Karmele (Avances en Supervisión Educativa, 2018)
The main aim of the present article is to provide a number of ideas and key elements about the conceptualization of inclusive school. For that purpose, different authors have been mentioned and the terms equity and inclusion have been defined.The inclusive school paradigm affects the vision of the school environment as a whole, in order to ensure that students can acces and participate in their learning processes. Moreover, in this article a model of intervention plan and its related elements have been posed.The importance and relevance when training the different professionals has been also emphasized, mainly concerning their professional development and the improvement of the organizations themselves.Lastly, and consideryng the inclusive perspective, some key elements have been pointed out regarding the aforementioned proposals and their subsequent supervision
Keywords: learning; equity; inclusion; intervention plan; participation; supervision